Fast-track Rehabilitation Accelerates Recovery After Laparoscopic Colorectal Surgery - Khoury, Wisam (JSLS, 2014)
BACKGROUND: Fast-track (FT) rehabilitation protocols have been shown to be successful in reducing both hospital stay and postoperative complications, as well as enhancing overall postoperative patient recovery. We are reporting the outcomes of our first group of patients undergoing colorectal surgery following the FT protocol. PATIENTS AND METHODS: We performed a prospective study of patients, between January 1, 2007 and January 31, 2010, who underwent laparoscopic colorectal resections in accordance with the guidelines of FT rehabilitation protocol. Recovery parameters including time to removal of naso-gastric tube and urinary catheter, time to bowel function and to resume diet, and length of hospital stay were evaluated. Postoperative outcomes, that is, postoperative complications and mortality, reoperations, and readmissions were also studied. RESULTS: A total of 71 patients, 30 women and 41 men, underwent FT rehabilitation for laparoscopic colorectal surgery. The mean age of the patients was 60 ± 16 years. The most common surgical procedures were right hemicolectomy 30% and anterior resection 27%. Liquid and regular diet were initiated on postoperative day 1.2 ± 0.4 and 2.1 ± 0.4, respectively. Overall postoperative morbidity was 8.5%. The mean length of stay was 4.4 ± 1.7 days, with only 3 readmissions. Forty-five patients fulfilled the FT care plan and were discharged on postoperative day 3. No reoperations or mortality were observed. CONCLUSIONS: FT rehabilitation results in favorable postoperative outcomes. Our data provides evidence and suggests that FT protocols should be implemented as a reliable method of preparation and recovery for laparoscopic colorectal surgery.